Regional Geochemical Prospection for Minerals in Chitral, Northern Pakistan - Khaliq, Abdul; Moon, C.J.; Khattak, M.U.K. (Journal of Himalayan Earth Sciences, 1997)
A comprehensive regional geochemical survey was carried out in Upper Chitral area. This survey was based on panned concentrates sampling techniques, during which a total of68 samples were collected from most of major rivers and their tributaries covering an area of more than 1000 km2 The aim of this geochemical investigation was to determine metals dispersion, their relation to mineralization, and regional distribution in the drainage system of the area. Our research reveals that Chitral area has a high potential for mineralization. Some valleys contain polymettalic anomalies while others have either precious or base metals. Strong anomalies of precious and base metals, together with As and Sb were detected in the northernmost part (Tirich Gol valley) of the surveyed area in which the respective ranges of Au, Ag, As, Sb, Cu, Pb, and Zn are 20-2500 ppb, 2-22 ppm, 2-1500 ppm, 1-18 ppm, 50-400 ppm, 100-1200 ppm, and 50-550 ppm. The significant mineral occurrences are found north of Reshun Formation. The central part (Barum, Pasti and Shoghor) of the survey area shows polymetallic signature with significant enrichment of precious metals Au=l0-200ppb, Ag=l-12 ppm, As=10-200 ppm and 1-10 ppm). The southern part, mainly Kafiristan valley, is high in Pb (100-1800 ppm) with some anomalies of Au (1-100 ppb) and Ag (2-17 ppm). New targets for mineral prospecting were located at several localities of Chitral valley. Important regional structures, such as faults, and their significance regarding mineralization were also defined during this investigation.